A process for production of nano-PbO from spent automobile lead-acid battery (2017)
The present invention provides an improved process for synthesis of lead organic compound from spent automobile lead-acid battery as precursor for production of nano-PbO. In the method, a survey of lead-acid battery types in South-Western Nigeria is made and spent lead- acid batteries are collected. The batteries are dismantled and the paste therefrom, which contains PbSO4, Pb3O2SO4, PbO2, PbO and Pb is separated. The paste is slurred to test acidity, is screened to a particular particle size, and its lead components are simultaneously desulphurised, leached, reduced and precipitated as lead organic compound. The desulphurising and leaching solutions are first mixed, then the paste is added, and then the reducing agent. The precipitated lead precursor is subjected to calcination process to yield purified nano-structured lead (II) oxide (nano-PbO), which can be used to produce new automobile battery.